Computation of Capacity Benefit Margin using Differential Evolution. (14th December 2010) - Rajathy, R.; Gnanadass, R.; Manivannan, K.; Kumar, Harish
In a competitive electric power market, the knowledge of Available Transfer Capability (ATC) can help power marketers, sellers and buyers in planning, operation and reserving transmission services. Capacity Benefit Margin (CBM) is an important factor in the calculation of ATC, without which ATC may be overestimated and this will lead to the risk of having generation unreliability. In this paper, a new algorithm using Differential Evolution along with Monte Carlo is proposed to evaluate CBM. The superiority of the proposed algorithm is tested on modified IEEE 30 bus system, over PSO.